Maju Chicken Farms Enterprise / Azali Daud … [et al.] - Daud, Azali; Jamadi, Aziz Isfarain; Jundam, Mohd Fazli; Mohamad, Mohd Khairul Azlan (2005)
With the name of Allah, the most Graceful and Merciful, for the Greatest. All the praise is to Allah and peace is upon the holy prophet Muhammad S.A.W, his family and his companions. With His permission, the business plan of ETR 300 is successfully completed. In this ETR project, we supply livestock chickens where our company's name is Maju Chicken Farm Enterprises. Maju Chicken Farm is a partnership that have four members. Our business is processing and selling chickens. This business will be operating at Pulau Indah, Selangor Darul Ehsan. Operation of our company will be starting on 13 May 2006. It is because in a year, we need to prepare the capital to build hen-houses and others equipments relative to the business. Thereafter, a signing of contract with Pertanian Pertiwi Sdn.Bhd is done as our primary supplier of raw materials. After that to complete our capital, we must submit a paper work to get loan from bank. Actually we are still confident that this business can expand and grow. It is because, young entrepreneurs are not interested in running this business as this business involves a lot of money and hard work. Therefore, we have a contract from Pertanian Pertiwi Sdn.Bhd which helps us to supply chick, vitamins, substance bran, and also buy 90% of our chickens. The other 10% will be sold to several target locations. The business location is very strategic to build a Hen-House because the location is far from a housing area while facilities such as, electricity, water and transportation route are easily accessible. With our involvement in this project, it gives us a clearer perception on how the business is done. It is compulsory for us to do a research, study and analysis of the business plan to ensure everything worked out as planned. Nevertheless, what we gain from this project can be applied in the future.